Infant Rhesus Macaque Brain α-Tocopherol Stereoisomer Profile Is Differentially Impacted by the Source of α-Tocopherol in Infant Formula. Issue 9 (2nd July 2020) - Kuchan, Matthew J; Ranard, Katherine M; Dey, Priyankar; Jeon, Sookyoung; Sasaki, Geoff Y; Schimpf, Karen J; Bruno, Richard S; Neuringer, Martha; Erdman, John W
ABSTRACT: Background: α-Tocopherol (αT) in its natural form [2′ R, 4′ R, 8′ R αT ( RRR- αT)] is more bioactive than synthetic α-tocopherol ( all rac- αT). All rac -αT is widely used in infant formulas, but its accretion in formula-fed infant brain is unknown. Objective: We sought to compare αT and stereoisomer status in infant rhesus macaques ( Macaca mulatta ) fed infant formula (RRR -αT or all rac -αT) with a reference group fed a mixed diet of breast milk and maternal diet. Methods: From 1 d after birth until 6 mo of age, infants ( n  = 23) were either nursery reared and exclusively fed 1 of 2 formulas by staff personnel or were community housed with their mothers and consumed a mixed reference diet of breast milk (69 mL/d at 6 mo) transitioning to monkey diet at ∼2 mo (MF; n  = 8). Formulas contained either 21 μmol RRR -αT/L (NAT-F; n  = 8) or 30 μmol all rac -αT/L (SYN-F; n  = 7). Total αT and αT stereoisomers were analyzed in breast milk at 2, 4, and 6 mo and in monkey plasma and liver and 6 brain regions at 6 mo of age. α-Tocopherol transfer protein (α-TTP), lipoprotein αT, and urinary α-carboxyethyl-hydroxychroman (α-CEHC) were measured. One-way ANOVA with Tukey's post-hoc test was used for analysis. Results: At study termination, plasma, liver, lipoprotein, and brain total αT did not differ between groups. However, the NAT-F–fed group had higher RRR -αT than the SYN-F–fed group ( P  < 0.01) and the MF group ( P  < 0.0001) in plasma (1.7- and 2.7-fold) and brain (1.5- and 2.5-fold). Synthetic αT 2 R stereoisomers (SYNTH-2 R ) were generally 3- and 7-fold lower in brain regions of the NAT-F group compared with those of the SYN-F and MF groups ( P  < 0.05). SYNTH-2 R stereoisomers were 2-fold higher in MF than SYN-F ( P  < 0.0001). The plasma percentage of SYNTH-2 R was negatively correlated with the brain percentage of RRR -αT (r = −0.99, P  < 0.0001). Brain αT profiles were not explained by α-TTP mRNA or protein expression. Urine α-CEHC was 3 times higher in the NAT-F than in the MF group ( P < 0.01 ). Conclusions: Consumption of infant formulas with natural (NAT-F) compared with synthetic (SYN-F) αT differentially impacted brain αT stereoisomer profiles in infant rhesus macaques. Future studies should assess the functional implications of αT stereoisomer profiles on brain health.